Beautiful light : religious meaning in film - Anker, Roy M. (Grand Rapids, Michigan : William B. Eerdmans Publishing Company, 2017)
Though "religious" films usually don't get much respect in Hollywood, religion still regularly finds its way into the movies. In Beautiful Light Roy Anker seeks out the often unnoticed connections between film and religion and shows how even films that aren't overtly religious or Christian in their content can be filled with deep religious insights and spiritual meaning. Closely examining nine critically acclaimed films, including Magnolia, The Apostle, American Gigolo, and M. Night Shyamalan's Wide Awake, Anker analyzes the ways in which these movies explore what it means to be human--and what it means, as human beings, to wrestle with a sometimes unwieldy divine presence. Addressing questions of doubt and belief, despair and elation, hatred and love, Anker's work sheds "beautiful light" on some of Hollywood's most profound and memorable films. -- From back cover.
Introduction : Through wonder to veneration -- "Not all angels have wings" : wonder, light and love in M. Night Shyamalan's Wide Awake -- And the blind shall see : grasping the radiance of being in The Color of Paradise -- The education of a one-man preaching machine : the realization of love in The Apostle -- Love's pure light : moral light and reconciliation in Dead Man Walking -- When hope breaks out : love and redemption in The Shawshank Redemption -- "It's take me so long to find you" : search and rescue in Paul Schrader's American Gigolo -- "How high can I fly?" : murder and sacramental ascent in Tom Tykwer's Heaven -- "It can happen" : frogs, deliverance, and reconciliation in P.T. Anderson's Magnolia -- "The glory smiling through" : wonder and beauty in The Thin Red Line."
Includes bibliographical references and index.
Includes filmography.
Print version record.
Master record variable field(s) change: 082
Keywords: Religion in motion pictures; Religion in motion pictures; PERFORMING ARTS / Reference; Religion in motion pictures; Electronic books; Electronic books